POTENTIAL NATURAL PRODUCTS WITH ANTICANCER PROPERTIES AND THEIR APPLICATIONS: Potential anticancer natural products - BALABHASKAR R; RAJENDRA KUMAR A; SELVARAJAN S; FARIDHA A; GAYATHRI GUNALAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Natural products continue to be a source for the discovery of drugs and drug leads even from ancient period. 80% of drug molecules have been obtained from either natural products or derivatives of the natural product. It has been found that the concept of a single drug for treating single disease may become outdated in the near future and the need of polyherbal formulations, as an alternate remedy is under investigation. Medicinal and aromatic plants contain biologically important phytochemicals, which have known curative properties. They are found as secondary metabolites in plants. Plants also contain certain other compounds that moderate the effects of the active ingredients. Medicinal and aromatic plants have their own contribution toward the treatment of both noncommunicable and communicable diseases. A survey done by the WHO indicates that a majority of the world population tends to use plants for treating diseases. Cancer, the second largest cause of death after cardiovascular disease accounts for about 3500 million people globally. Due to the serious side effects of synthetic chemopreventive agents, research is going onto investigate the nature derived chemopreventive agents. In addition to the plant-derived compounds, marine, and animal resources also play an important role as clinically beneficial anticancer agents with minimal or no toxicity. The best examples for plant-derived compounds include vincristine, vinblastine, irinotecan, etoposide, and paclitaxel; they have a different mode of action against cancer such as interaction with microtubules, inhibition of topoisomerases I or II, alkylation of DNA, and interference with tumor signal transduction. The natural products from marine sources such as bryostatin, squalamine exhibit a significant antimitotic, and anti-angiogenic activities. The benefits of various anticancer drugs derived from natural products are the fact that it can have its effect on cancer cells alone without harming healthy cells, which is unlikely to be the case with other conventional chemotherapeutics. In this review, various natural products and their anticancer properties have been discussed briefly.